Taiwanese EFL learners’ English proficiency, intercultural competence, and willingness to communicate - Cathleen Wijaya Miauw; Yi-Huey Guo (Journal on English as a Foreign Language, 2021)
Although issues on intercultural competence and willingness to communicate have been largely studied, most studies focused on learners’ personality traits, motivation, or communication apprehension as affected factors. The significant relationship between intercultural competence, willingness to communicate, and learners’ English proficiency was less addressed. This study hereby examined the relationship of these three. It drew on quantitative research by employing a questionnaire to 409 Taiwanese college freshmen studying at one Taiwanese university (216 high- & 193 low-English-proficiency). A printed questionnaire of fifty-two items with the use of the five-point Likert-scale was adopted. The result showed significant differences between high- and low-proficiency students’ intercultural competence and willingness to communicate. Students of high English proficiency showed more intercultural competence and willingness to communicate. They demonstrated sophistication in operating their skills of intercultural competence and were more confident in communicating with people of different cultures in English. This study also found that learners’ growth of intercultural competence and willingness to communicate were interconnected per se; this interconnectedness was evident on both high- and low-proficiency groups. This study adds new threads to relevant studies and suggests that language teachers seek ways to enhance their students’ intercultural competence and willingness to communicate.